A COMMON FIXED POINT THEOREM VIA FAMILY OF R-WEAKLY COMMUTING MAPS - Singh, D.; Ahmed, A.; Singh, M.; Tomar, S. S. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2013)
In the present paper we prove a unique common fixed point theorem for a family of R-weakly commuting maps in non-Archimedean Menger PM-spaces without using the notion of continuity. our result generalizes and extends the result of Khan and Sumitra [5] and other, also suggest a path to a new inequality containing rational, product and minimum of some terms under implicit relation.